2017
DOI: 10.1136/bmjopen-2016-013817
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco control environment: cross-sectional survey of policy implementation, social unacceptability, knowledge of tobacco health harms and relationship to quit ratio in 17 low-income, middle-income and high-income countries

Abstract: ObjectivesThis study examines in a cross-sectional study ‘the tobacco control environment’ including tobacco policy implementation and its association with quit ratio.Setting545 communities from 17 high-income, upper-middle, low-middle and low-income countries (HIC, UMIC, LMIC, LIC) involved in the Environmental Profile of a Community's Health (EPOCH) study from 2009 to 2014.ParticipantsCommunity audits and surveys of adults (35–70 years, n=12 953).Primary and secondary outcome measuresSummary scores of tobacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 43 publications
0
32
1
Order By: Relevance
“…Many countries have adopted stronger restrictions on tobacco marketing than the USA, and some Vector measures in the PhenX Toolkit are included in routine international surveillance instruments, such as the Global Youth and Adult Tobacco Surveys and surveys by the ITC Policy Evaluation Project in 29 countries 44. Even the price of the cheapest cigarette pack from the STARS instrument can be compared with data collected in urban and rural neighbourhoods across low-income, middle-income and high-income countries using the Environmental Profile of a Community’s Health (EPOCH), which assesses environmental determinants of cardiovascular health 45. In addition, one adaptation of a widely used ITC scale46 has incorporated information about the retail availability of tobacco from EPOCH community assessments 45…”
Section: Discussionmentioning
confidence: 99%
“…Many countries have adopted stronger restrictions on tobacco marketing than the USA, and some Vector measures in the PhenX Toolkit are included in routine international surveillance instruments, such as the Global Youth and Adult Tobacco Surveys and surveys by the ITC Policy Evaluation Project in 29 countries 44. Even the price of the cheapest cigarette pack from the STARS instrument can be compared with data collected in urban and rural neighbourhoods across low-income, middle-income and high-income countries using the Environmental Profile of a Community’s Health (EPOCH), which assesses environmental determinants of cardiovascular health 45. In addition, one adaptation of a widely used ITC scale46 has incorporated information about the retail availability of tobacco from EPOCH community assessments 45…”
Section: Discussionmentioning
confidence: 99%
“…). With regard to public health, higher quit ratios are associated with greater tobacco control policies (eg, price, health warnings), social unacceptability of smoking and knowledge of smoking-related effects on health68 so research may help to determine the effectiveness of these public health initiatives for persons with cannabis use or CUDs who smoke cigarettes. Based on our results, both public health and clinical efforts to improve cigarette quit outcomes may benefit from including those with any cannabis use.…”
Section: Discussionmentioning
confidence: 99%
“…105,106 In PURE, we have observed that the implementation of policies to control tobacco use (eg, higher cigarette costs, lower availability, antismoking signage, and bans on tobacco advertising) was more prevalent in HICs compared with MICs or LICs, and where all these measures are combined, there are higher quit rates among smokers. 107 Agricultural policies, coupled with advances in agricultural technology, have greatly changed the food supply in most HICs, resulting in greater availability and consumption of refined carbohydrates, vegetable oils, processed foods, sugary beverages, and meats, with similar trends in the global food system now impacting MICs and LICs to variable degrees. 79 In MICs and LICs, healthy dietary choices are a further challenge to adhere to on a long-term basis because healthy diets are not practicable or affordable because of the unaffordability of many healthy foods (eg, fresh fruit and vegetables).…”
Section: Strength Of Evidence: Highmentioning
confidence: 99%